Development of Spatial.io-Based GeoRivers Learning Media in Sub-Material of Dynamics of Land Waters on River Surface - Oktavia, Wita; Yuswanti Ariani Wirahayu (Global Action and Education for Society, 2026)
Learning media has an important role in the teaching and learning process in schools. Currently, teachers are expected to have skills in media literacy and the use of learning technology. Teachers need to adapt and utilize technology to create an effective learning process. This research aims to develop GeoRivers learning media based on the Spatial.io platform in the sub-material of Dynamics of Land Waters on the River Surface for grade X students. The research subjects for the media development trial were students of class XI IPS 2 MA Bilingual Batu which amounted to 26 students. The results of the needs analysis that have been carried out through observation, interviews, and questionnaires show that there is a need for innovation in learning media such as interactive digital media. The validation test involved media and material experts. The results of the media validation test showed that this media was very valid with scores of 87.59% and 89.11% in the material validation test. The results of the response by the students obtained a score of 90.38% (very good). The results of this study show that Spatial.io-based GeoRivers learning media is very feasible to be used in Geography learning. However, this study is still limited to the attractiveness and feasibility aspects, so further studies are needed to test its effectiveness thoroughly.